2013
DOI: 10.1051/0004-6361/201219032
|View full text |Cite
|
Sign up to set email alerts
|

Case study of a complex active-region filament eruption

Abstract: Context. We investigated a solar active-region filament eruption associated with a C6.6 class flare and a coronal mass ejection (CME) in NOAA active region 08858 on 2000 February 9. Aims. We aim to better understand the relationship between filament eruptions and the associated flares and CMEs. Methods. Using BBSO, SOHO/EIT, and TRACE observational data, we analyzed the process of the active-region filament eruption in the chromosphere and the corona. Using the SOHO/MDI magnetograms, we investigated the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Solar filaments/prominences are one of the most common structures in the corona, which may lead to energetic coronal mass ejections (CMEs) and flares when they erupt (Chen & Shibata 2000;Forbes 2000;Lin & Forbes 2000;Yan et al 2013;Xue et al 2016;Yang et al 2017). They appear at the limb as bright features called prominences.…”
Section: Introductionmentioning
confidence: 99%
“…Solar filaments/prominences are one of the most common structures in the corona, which may lead to energetic coronal mass ejections (CMEs) and flares when they erupt (Chen & Shibata 2000;Forbes 2000;Lin & Forbes 2000;Yan et al 2013;Xue et al 2016;Yang et al 2017). They appear at the limb as bright features called prominences.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, transient X-ray brightenings, so-called preflares, are observed before the flares (Chifor et al 2007;Sterling et al 2011), which are coincident with magnetic cancellation or emerging magnetic flux (Schmieder et al 2008). Moreover, Yan et al (2013) suggested that the brightening in the chromosphere before the filament expansion may indicate the onset of TC reconnection. And Chen et al (2018) detected obvious brightenings in UV bands and hot outflows in the chromosphere, which showed the preflare reconnection process of the partial eruptions.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Typically, filament eruptions are preceded by their precursor activities (Chen 2011), such as darkening and widening (Martin 1980), reconnection-favored emerging flux (Feynman & Martin 1995), large-amplitude oscillation (Chen et al 2008;Zhang et al 2012), heating and particle acceleration (Hernandez-Perez et al 2019), and soft X-ray (SXR) brightening (Mitra et al 2020). In addition, EUV or chromosphere brightenings inside the filament or its close vicinity are also considered as precursors (Sterling & Moore 2005;Alexander et al 2006;Sterling et al 2011;Yan et al 2013;Wang et al 2018;Devi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With typical temperatures of around ∼6000 K and densities of ∼10 11 cm −3 (Munro et al 1979;Gopalswamy et al 2003;, they are usually located above magnetic polarity inversion lines (PILs) and are believed to be supported by the magnetic tension force provided by concave upward magnetic dips (Low & Hundhausen 1995;Démoulin & Aulanier 2010;Ichimoto et al 2023). When disturbed, they can undergo eruptions and result in the formation of flares and coronal mass ejections (CMEs), which can have significant impacts on the Earth and planetary space environments (Yan et al 2013;Sun et al 2022;Yang et al 2023). Therefore, investigating the eruption processes of solar filaments is essential for a better understanding of their effects on space weather.…”
Section: Introductionmentioning
confidence: 99%